“I sometimes have doubts about the news on Facebook”: Adolescents’ encounters with fake news on the internet - Vissenberg, Joyce; d’Haenens, Leen (UI Scholars Hub, 2020)
Fake news is increasingly present on the internet and on social media, and youths, who mainly follow the news on these platforms, are at risk of being misinformed and deceived. This study aims to serve as an important knowledge base about adolescents’ definitions of, experiences with, and opinions about fake news on the internet. A qualitative content analysis of open-ended survey responses regarding experiences with fake news online among 214 Flemish youths (aged 15 to 19) provides insight into the sources of fake news, the topics covered in fake news, and the characteristics of fake news according to these youths. This study contributes to the field by giving insight into adolescents’ experiences with fake news and serves as an important base for further research into youths and fake news on the internet.